Task allocation and innovation: Revisiting the role of vocational education and training in manufacturing firms - Eike Matthies; Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2025)
This paper examines the individual innovation contributions of the vocational education and training (VET) workforce compared to university graduates such as scientists and engineers. For this purpose, individual-level data from the German manufacturing sector are used, distinguishing between persons with initial and higher VET qualifications. The empirical results on various input and output indicators show that the VET workforce is not only involved in the implementation phase of the firm's innovation process, but also makes a relevant contribution to the invention phase. Moreover, the empirical evidence suggests a certain division of labour between VET employees and university graduates, which is more likely to occur in large firms due to their higher degree of functional specialisation and task differentiation among employees. There is also some evidence to support the hypothesis that employees with higher VET qualifications, such as master craftsmen or technicians, act as 'boundary spanners' throughout the innovation process, ensuring that effective interactive learning can take place between VET employees from the shop floor and academically trained R&D personnel, so that the benefits of educational workforce diversity can be realised. The paper concludes with implications for policy, management and further research. – – In diesem Beitrag werden die individuellen Innovationsbeiträge von Erwerbstätigen mit Qualifikationen aus dem Berufsbildungssystem im Vergleich zu Erwerbstätigen mit akademischen Qualifikationen (z.B. Wissenschaftler und Ingenieure) untersucht. Dazu werden Daten auf Personenebene aus dem Verarbeitenden Gewerbe verwendet, wobei u.a. zwischen Personen mit einer beruflichen Erstausbildung und Personen mit einem höheren beruflichen Bildungsabschluss wie Meister oder Techniker unterschieden wird. Die empirischen Ergebnisse zu verschiedenen Input- und Outputindikatoren zeigen, dass beruflich Qualifizierte nicht nur in der Umsetzungsphase des betrieblichen Innovationsprozesses beteiligt sind, sondern auch in der Inventionsphase relevante Innovationsbeiträge leisten. Darüber hinaus deuten die empirischen Ergebnisse auf eine gewisse Arbeitsteilung zwischen beruflich Qualifizierten und Hochschulabsolventen hin, die aufgrund des höheren Grades an funktionaler Spezialisierung und Aufgabendifferenzierung eher in Belegschaften größerer Unternehmen anzutreffen ist. Es gibt auch Anzeichen für die Gültigkeit der Hypothese, dass Beschäftigte mit höherer beruflicher Bildung während des Innovationsprozesses als wichtige "Schnittstelle" fungieren und sicherstellen, dass effektives interaktives Lernen zwischen Beschäftigten mit beruflicher Erstausbildung aus der Produktion und akademisch ausgebildetem F&E-Personal stattfinden kann. Der Beitrag schließt mit Schlussfolgerungen für Politik, Management und weitere Forschung.
Keywords: I2; J24; M53; O15; O30; O31; 330; Innovation; Vocational education and training (VET); Skills; Diversity; Firm size